STUDI PEMBUATAN SNACK FOOD BAR BERBAHAN DASAR SACHA INCHI (PLUKENETIA VOLUBILIS L.) DENGAN PENAMBAHAN TEPUNG SUKUN (ARTOCARPUS COMMUNIS) - Muti, Nurfadila; Salimi, Yuszda K; Kasim, Rahmiyati (Universitas Negeri Gorontalo, 2025)
Sacha inchi (Plukenetia volubilis L.) and breadfruit flour (Artocarpus communis) are nutrient-rich local food ingredients with great potential for development as functional food products. This study aimed to develop a snack food bar based on sacha inchi paste and breadfruit flour with an optimal formulation that meets nutritional standards and consumer preferences. The research employed a D-optimal mixture design with three main variables: sacha inchi paste, breadfruit flour, and chopped sacha inchi beans. The formulation process was followed by proximate analysis, antioxidant activity testing using the DPPH method, and organoleptic evaluation covering taste, aroma, color, and texture attributes. Results showed that the optimal formulation consisted of 43.818% sacha inchi paste, 41.197% breadfruit flour, and 14.985% chopped sacha inchi beans, yielding 479.63 kcal per 12 bars. The product exhibited high protein and fat content and demonstrated moderate antioxidant activity (IC₅₀ = 67.06 ppm). Organoleptic testing indicated favorable consumer acceptance, particularly in color and taste. These findings suggest that the combination of sacha inchi paste and breadfruit flour can produce a nutritious and functional snack food bar. The product development contributes to local food diversification and the commercialization potential of competitive tropical ingredients. Snack food bar is one of the snacks in the form of a rod that generally consists of flour equipped with fillers such as fruits, nuts, jam and honey. This study aims to determine the chemical and organoleptic characteristics of snack food bars made from sacha inchi bean paste and breadfruit flour. Pre-treatment in the manufacture of snack food bars is the result of formulation from the results of a mixture design (D-optimal)12 formulation that has a concentration of sacha inci bean paste, breadfruit flour. From the results of the 14 raw material formulas. This study uses a mixture design (D-optimal) 12. The optimization of the formulation of raw materials for making snack food bars in this study was carried out to produce a total energy value of 405.046 kcal while the parameters of the protein content value were 14.01%, fat content was 28.85%, carbohydrate content was 40.96%, moisture content was 14.45%, ash content was 1.72%, fiber content was 2.06% and antioxidant activity was 67.06 ppm. Organoleptic testing produces snack bars with ra rating Keywords: Snack Food Bar, Sacha Inchi Beans, Breadfruit Flour, Total Energy ABSTRAKSacha inchi (Plukenetia volubilis L.) dan tepung sukun (Artocarpus communis) merupakan bahan pangan lokal yang kaya nutrisi dan berpotensi dikembangkan sebagai produk pangan fungsional. Penelitian ini bertujuan untuk mengembangkan snack food bar berbasis pasta kacang sacha inchi dan tepung sukun dengan formulasi optimal yang memenuhi standar gizi dan disukai konsumen. Metode yang digunakan adalah mixture design tipe D-optimal dengan tiga variabel utama, yaitu pasta kacang sacha inchi, tepung sukun, dan kacang sacha inchi. Proses formulasi diikuti oleh analisis proksimat, pengujian aktivitas antioksidan menggunakan metode DPPH, serta uji organoleptik terhadap atribut rasa, aroma, warna, dan tekstur. Hasil menunjukkan bahwa formulasi optimal mengandung 43,818% pasta kacang sacha inchi, 41,197% tepung sukun, dan 14,985% kacang cincang, dengan energi sebesar 479,63 kkal per 12 bar. Produk ini memiliki kadar protein dan lemak tinggi serta menunjukkan aktivitas antioksidan sedang (IC₅₀ = 67,06 ppm). Uji organoleptik menunjukkan penerimaan baik, terutama pada warna dan rasa. Temuan ini menunjukkan bahwa kombinasi pasta kacang sacha inchi dan tepung sukun dapat menghasilkan snack food bar bergizi dan fungsional. Pengembangan produk ini berkontribusi pada diversifikasi pangan lokal dan potensi komersialisasi berbasis bahan tropis berdaya saing tinggi.